Improving Students Activity and Students Learning Outcomes by Using Problem Centered Learning (PCL) Setting Numbered Head Together (NHT) - Siti Nihayaturrahmah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to know the improving of students activities by using problem centered learning (PCL) setting numbered head together (NHT) learning model. To know the improving of student learning outcomes by using problem centered learning (PCL) setting numbered head together (NHT) learning model.  The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIIA at MTs Al Firdaus Suci Panti. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: PCL, NHT,  students activity, and students learning outcomes